(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article provides information about the use of modern pedagogical technologies in classes at schools and universities, the relationship between teachers and students, and the role of modern pedagogical technologies in the organization of English language classes.